2016
DOI: 10.1515/bhk-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Sauna-induced body mass loss in physically inactive young women and men

Abstract: SummaryStudy aim: The aim of this study was to evaluate the relationship between basic somatic features (body mass and height) and body mass loss in physically inactive young women and men exposed to thermal stress in a dry sauna. Materials and methods:The research was conducted in 2015 on 685 first-year full-time students (333 women, 352 men), aged 19-20 years old. Nude body mass was measured after the students dried off before and after using the sauna.Results: An analysis of regression equations indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…BML values were very high in overweight and obese males and females and were approximately twofold higher than in underweight women, with similar correlations were noted in men [19]. In our previous study [18], BML values measured after sauna bathing were significantly higher in female and male subjects with higher body mass, but they tended to be lower in taller participants (less so in men). With every kilogram increase in body mass, the corresponding BML values increased by 0.0144 kg in women and 0.0146 kg in men on average.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…BML values were very high in overweight and obese males and females and were approximately twofold higher than in underweight women, with similar correlations were noted in men [19]. In our previous study [18], BML values measured after sauna bathing were significantly higher in female and male subjects with higher body mass, but they tended to be lower in taller participants (less so in men). With every kilogram increase in body mass, the corresponding BML values increased by 0.0144 kg in women and 0.0146 kg in men on average.…”
Section: Discussionsupporting
confidence: 71%
“…Dry sauna leads to changes in physiological parameters as well as body composition. Sauna bathing induces sweating, which promotes passive dehydration and leads to hyperthermia [18], mainly due to the evaporation of sweat and enhanced blood circulation in the skin, the main cooling mechanism in the body [4]. Uncontrolled sweating leads to body mass loss (0.1-1.0 kg), and fluid loss can reach up to 13 liters under extreme circumstances, such as sauna competitions [38].…”
Section: Introductionmentioning
confidence: 99%
“…Podstawski et al [ 14 ] reported that overweight subjects lost more body weight compared to normal-weight subjects. Similarly, Podstawski et al [ 27 ] reported that higher body mass leads to a significant increase in sauna-bath-induced body mass loss, stating that body mass had a significant influence on body mass loss. Moreover, Podstawski et al [ 14 ] observed that energy expenditure and body mass loss were correlated with anthropometric parameters and body composition parameters (percentage of body fat, body fat mass, and visceral fat level).…”
Section: Discussionmentioning
confidence: 99%
“…The studies that have observed the effects of sauna baths on body composition have been carried out on sedentary and overweight people [ 13 , 14 , 27 ]. In addition, the temperature used in the studies mentioned above was lower than in the present study and involved fewer sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Finnish sauna bathing involves brief exposure to high environmental temperature (80°C–100°C), and it has long been used for pleasure, wellness, and relaxation ( Laukkanen et al, 2018 ). There is ample evidence to suggest that regular sauna use by healthy individuals, persons with health problems and athletes exerts beneficial effects as a form of heat therapy and biological regeneration ( Biro Masuda et al, 2003 ; Pilch et al, 2014 ; Podstawski et al, 2016 ; Scoon et al, 2007 ; Sutkowy et al, 2017 ). Regular sauna bathing may alleviate and prevent the risk of both acute and chronic diseases ( Laukkanen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%